Factors influencing the nematode community during composting and nematode-based criteria for compost maturity. (February 2018) - Steel, H.; Moens, T.; Vandecasteele, B.; Hendrickx, F.; De Neve, S.; Neher, D.A.; Bert, W.
Highlights: Nematodes showed a repeatable and predictable succession during composting. The microbial succession (PLFA data) was not related to changes during the process. Nematode succession was related to composting phases, temperature and duration. Supported by 4 nematode based criteria an index for compost maturity was developed. Abstract: Pilot studies indicate that shifts in the nematode species composition, life strategies and feeding behavior during composting appear to be fairly consistent and, therefore, promising as a potential tool to assess compost maturity. However, this has been only based on a limited number of, mainly, non-replicated observations. In this study, we tested whether the nematode community succession patterns are recurrent for parallel processes and assessed the relationship between the changes in the nematode community and potential important variables (i.e., temperature, duration of composting and the microbial community). The nematode and microbial community of three simultaneously running Controlled Farm Composting and a reference Green Waste composting process were analyzed through time. Bacterial-feeding enrichment opportunists were most numerous during and directly after the heat peaks. Subsequently, the bacterial-feeding/predator community dominated and the fungal-feeding nematodes became more dominant during maturation, confirming general community patterns from previous experiments. Nematode abundances significantly fluctuated with temperature and the relative abundance of fungal-feeding nematodes increased as the duration of the curing process increased. The amount of fungal-feeding nematodes was associated significantly with both duration of composting and temperature, and the F/(F + B) ratio was only significantly associated with duration of composting. Based on these results, and additional data from an industrial reference compost process and on available literature, a Nematode-based Index of Compost Maturity (NICM) is proposed, combining four nematode-based criteria (i.e., nematode abundance, F/(F + B) ratio, the presence of more than one fungal-feeding taxon and the presence of diplogasterids). Nevertheless, the NICM should be considered as work in progress which should be tested for a wider range of composts from diverse feedstock mixtures, locations (sites) and composting techniques, to validate the use of the index and allow more reliable interpretation of particular values of this index.